Incidence and risk of endocrine and metabolic abnormalities linked to PARP inhibitors in solid tumors: a meta-analysis - Shunlian Fu; Pingjin Zou; Zengyi Fang; Xinxiang Zhou; Junyang Chen; Cuicui Gong; Li Quan; Bing Lin; Qiu Chen; Jinyi Lang; Meihua Chen (BMC Cancer)
Abstract Background Poly (ADP-ribose) polymerase inhibitors (PARPi) serve as crucial therapeutic agents in solid tumor treatment. Preclinical investigations suggest a potential protective function of PARPi against endocrine and metabolic impairments. Nevertheless, the existing body of evidence remains inconclusive on this aspect. Purpose Our aim was to evaluate the potential impact of PARPi on endocrine and metabolic disruptions in clinical trials. Data sources We conducted a comprehensive search across the Medline, EMBASE, PubMed, and Web of Science databases, along with the ClinicalTrials.gov registry. Study selection Phase II/III randomized controlled trials (RCTs) investigating the effects of PARPi in metabolic and endocrine processes were selected for inclusion in patients with solid tumors. Data extraction The primary outcomes of interest encompassed metabolic and endocrine dysfunctions. Data synthesis A total of 26 trials (n = 9,590 patients) were included in our meta-analysis. Niraparib demonstrated an increased risk of any-grade hyperglycemia (OR = 2.15, 95% CI 1.28–3.62), with patients receiving PARPi for metastatic pancreatic cancer showing a higher susceptibility to any-grade hyperglycemia (OR = 1.78, 95% CI 1.04–3.04). Conversely, rucaparib exhibited a potential ameliorative effect on hyperglycemia (OR = 0.54, 95% CI 0.30–0.97). No statistically significant disparities were observed for other outcomes associated with PARPi utilization. Limitations Among these RCTs included, 50% were assessed as low qualities due to high risk of bias. Conclusions Our meta-analysis demonstrated that PARPi may exert adverse effects on endocrine and metabolic pathways. Close monitoring of hyperglycemia is recommended for patients undergoing niraparib therapy, especially those with pancreatic cancer. Trial registration This meta-Analysis was prospectively registered in the PROSPERO database with ID CRD42023457959. Graphical Abstract